Experimental Study on Optimization of Polymer Preslug Viscosity of ASP Flooding in Interlayer Heterogeneous Well Group Artificial Sandstone Core - Qiji Sun; Kesen Yang; Guomin Xu; Shunde Yin; Chunsheng Wang (Geofluids)
An artificial sandstone core model of large well group of positive rhythmic heterogeneous reservoir was designed and made for the simulation of ASP flooding experiment in the moderate heterogeneous reservoir. The well layout of one injection and one production was employed for the core model, to simulate the influence of polymer preslugs with different viscosity on ASP flooding effect. The experimental results show that the injectability of the polymer preslug and the effect of relieving the conflict of remaining oil production in each layer are related to the viscosity of the system. In the heterogeneous core model with the coefficient of variation of 0.65, under the constraint of the same amount of polymer agent, the ASP flooding effect of the 0.075 PV, 60 mPa·s polymer preslug was better than that of the 0.093 PV, 40 mPa·s and 0.064 PV, 80 mPa·s polymer preslugs. The change in the viscosity of the polymer preslug did not enable the ASP system to effectively exploit the low-permeability layer though. As the viscosity increased, the pressure difference between injection and production increased; the remaining oil could be exploited effectively at the bottom of the high-permeability layer and the medium-permeability layer as well as the injection end of the medium-permeability layer. If the viscosity is too small, the high-permeability area cannot be effectively blocked by the injected chemical agent, and if the viscosity is too large, the injected chemical agent cannot produce good elastic displacement relationship, which will lead to ineffective chemical agent flow. Therefore, the polymer preslug viscosity of the ASP flooding system should be moderate, and cores with different heterogeneity should have a reasonable viscosity matching range.